The Ongoing Struggle for Agrarian Reform As an Unfinished Agenda? Lessons From Mekarsari Village - Abeng, Andi Tenri; Winoto, Joyo; Soetarto, Endriatmo; Asnawi, Yudha Heryawan; Hadijah, Sitti; Sita, Rai (BHUMI: Jurnal Agraria dan Pertanahan, 2023)
Abstract: Agrarian reform without interaction between the state and society only addresses temporary issues. The implementation of agrarian reform in Indonesia has been overly focused on achieving outputs based on easily measurable quantities, leaving social problems unaddressed. The aim of this research is to elaborate the implementation of agrarian reform, particularly in the management of assets in the Mekarsari Agrarian Reform Village. The method used is a quantitative approach using questionnaires and in-depth interviews with 50 respondents who are beneficiaries of agrarian reform. The data were then analyzed using descriptive statistics method. The results of the study indicate that the implementation of management at the planning, implementation, and monitoring and evaluation stages shows that the interaction between the responsibility of state actors and community participation is low. As a result, the implementation of agrarian reform is still one-way, limited to completing the output targets of land redistribution and granting access decided by the organizers. Without meaningful community participation, it will be difficult for the community to take control to decide on the appropriate use of resources. For this reason, the implementation of agrarian reform in Mekarsari Village still needs to be contested. Keywords: Agrarian reform, Contested, State-society interaction